P1-S5.31 Coinfection and concurrent sexually transmitted infections (STIs) in sexual partnerships: potential impact of partner notification and treatment in STD control. (10th July 2011) - Canchihuaman, F; Hawes, S; Holmes, K; Garcia, P; Carcamo, C
Abstract : Background: Partner notification and treatment has the potential to be one of the most important strategies in the control of STIs. However, studies indicate that this approach is not often used. Additionally, there is not much information about STIs among sexual partnerships. Objectives: To determine the prevalence of several STIs in sexual partnerships and to estimate the potential utility of partner treatment. Methods: We enrolled males and females 18–29 years of age from a random household sample in 24 cities in Peru and enrolled same-residence sex partners of the participants. Participants and partners responded to demographic and sexual behaviour questionnaires and provided biological samples tested for Neisseria gonorrhoeae, Chlamydia trachomatis, and Trichomonas vaginalis, syphilis, HSV-2 and HIV. Results: Of 2302 couples enrolled, 2163 couples had laboratory results available for either CT or TV and 1696 couples for either HIV, HSV-2 or early syphilis. CT, TV, early syphilis, HSV-2, and HIV were found in 7.1%, 4.4%, 1.2%, 24.8%, and 0.2% of couples, respectively. Among couples in which at least one subject was affected by a specific STIs, both partners had CT in 53 (39.3%) couples, TV in 22 (25.0%) couples, early syphilis in 3 (14.3%) couples, HSV-2 in 215 (51.1%) couples, and HIV in 2 (66.7%). Of couples affected by CT, 18/131(13.7%) had TV; 1/109 (1.3%) had early syphilis; 41/109 (41.6%) had HSV-2; and no one had HIV. Among females affected only by CT, 52.3% of partners had CT and 2.6% had TV; and among those only affected by TV, 13.7% of partners had CT and 26.2% had TV. Among males affected only by CT, 68.8% of partners had CT and 14.3% had TV; and among those affected only by TV, 11.5% of partners had CT and 84.6% had TV. Conclusions: A relatively high proportion of males and females affected by an STI had the same infection than their partners and not an infrequent number had different infections. Strategies to increase utilisation of partner notification and treatment may help STI control. Further review of partner treatment guidelines needs to be performed.